Bunda PAUD dan Pentingnya Literasi Dini di Kecamatan Katingan Kuala Kabupaten Katingan Kalimantan Tengah - Sumiati Sumiati (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
Early Childhood Education (PAUD) plays an important role in forming the foundation of children's education. In Katingan Kuala District, Katingan Regency, Central Kalimantan, the role of PAUD Mothers has been key in introducing and developing early literacy. The PAUD Mother Initiative also involves training for teachers and parents about the importance of early literacy, as well as how to create an environment that supports literacy at home. The impacts of early literacy include establishing a strong academic foundation, developing cognitive and social skills, increasing interest in reading, and supporting parental involvement in their children's education. This research uses a qualitative approach, with data collection methods in the form of in-depth interviews, participant observation and document analysis. The results show that the role of PAUD mothers in early literacy is very important, with the programs they run having had a significant positive impact on children's development. Continuous interaction between children, teachers and parents, supported by a conducive learning environment, is the key to the success of the early literacy program in Katingan Kuala District.